Enhancing Blood Profile and Performance of Broiler Supplemented with Biopeptide from Chicken Feet - Hartoyo, Bambang; Widyastuti, Titin; Rahayu, Sri; Santosa, R Singgih Sugeng (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
Feed manipulation by feeding additive aimed to produce safety and healthy livestock product. Bioactive peptide from chicken feed as one of solution to increase immune function without give any effect to host. This study aimed to evaluate addition of biopeptide from chicken feed to blood profile and performance of broiler. Two hundred one-day-old commercial broiler chicken and assigned to four treatments (0, 2, 4, and 6 %) with ad libitum water during research to evaluate treatment to parameter tested such as feed consumption, weight gain, leucocyte, lymphocyte, erythrocyte and monocyte. Five replication and ten trial unit of broiler used. Addition biopeptide from chicken feed until 6 % did not give any effect (p>0.05) to feed consumption, but there was significant (p<0.05) effect on daily weight gain, statistically. Meanwhile, 40 % dosage of biopeptide from chicken feed increased (p<0.05) quantity of lymphocyte of broiler. It is concluded that the addition of biopeptide enhanced immune of broiler without give any negative effect of broiler performance